Catholicism and American political ideologies: Catholic social teaching, liberalism, and conservatism - Krason, Stephen M. (Hamilton Books, 2017)
The nature of liberalism and conservatism, and their relationship to American Catholics -- A summary of Catholic social teaching from the social encyclicals and other church documents -- Comparing American liberalism and church teaching -- Comparing American conservatism and church teaching